2021
DOI: 10.1590/2175-7860202172037
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagação de Aechmea miniata e Aechmea blanchetiana

Abstract: Resumo Este trabalho teve o objetivo de avaliar a resposta morfogênica da micropropagação de Aechmea miniata e Aechmea blanchetiana após diferentes tratamentos com citocinina e auxinas. O estabelecimento in vitro se deu a partir de sementes de plantas adultas, com aproximadamente 2 anos de idade. Após descontaminação as sementes foram inoculadas em meio MS. Após 30 dias da germinação, foram isolados segmentos caulinares com aproximadamente 5 mm, e em seguida, foram transferidos para meio MS suplementado com BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Freitas Neto ( 2009) evaluated subcultures for in vitro multiplication of V. flavicans and found NSE lower than 2 in the first subculture and between 6 and 7 in the third subculture when using BAP at concentrations of 2.22 and 4.44 µM, which confirms that this cytokinin is efficient for in vitro production of Vellozia shoots. Garcia et al (2021) found that increases in BAP concentration increase the NSE in the bromeliad species Aechmea miniata (Beer) Baker and Aechmea blanchetiana (Baker) L. B. Smith, with the highest NSE of 14.5 for A. miniata and 10.5 for A. blanchetiana after 225 days when using 13.32 μM of BAP.…”
Section: Resultsmentioning
confidence: 95%
“…Freitas Neto ( 2009) evaluated subcultures for in vitro multiplication of V. flavicans and found NSE lower than 2 in the first subculture and between 6 and 7 in the third subculture when using BAP at concentrations of 2.22 and 4.44 µM, which confirms that this cytokinin is efficient for in vitro production of Vellozia shoots. Garcia et al (2021) found that increases in BAP concentration increase the NSE in the bromeliad species Aechmea miniata (Beer) Baker and Aechmea blanchetiana (Baker) L. B. Smith, with the highest NSE of 14.5 for A. miniata and 10.5 for A. blanchetiana after 225 days when using 13.32 μM of BAP.…”
Section: Resultsmentioning
confidence: 95%